Slots and Notches Loaded Microstrip Patch Antenna for Wireless Communication - Ashish Singh; Kamakshi Kamakshi; Mohd. Aneesh; J.A. Ansari (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In this article, the theoretical investigations are carried out on slots and notches loaded microstrip patch antenna for dual-band operations. The antenna parameters are calculated such as return loss, VSWR and radiation pattern. It is observed that antenna resonates at three distinct modes of frequencies of 1.490/1.953/2.941 GHz. The characteristics behaviors of the proposed antenna are compared with other coaxial fed microstrip patch antennas. The bandwidth of the proposed antenna at modes TM01 is 2.01 %( simulated) and 3.42 % (theoretical), TM02 is 1.10 %( simulated) and 3.81 % (theoretical) and TM03 is   1.01 % (simulated) and 4.80 % (theoretical). The theoretical results are compared with IE3D simulation results as well as reported experimental results and they are in close agreement. DOI:  http://dx.doi.org/10.11591/telkomnika.v13i3.7282